Marriage and Divorce in the Jewish State : Israel's Civil War. - Weiss, Susan M. (Brandeis Series on Gender, Culture, Religion, and Law & HBI Series on Jewish Women., 2012)
A comprehensive look at how rabbinical courts control Israeli marriage and divorce.